STUDY OF THE CRITICAL ANGLE OF CHANNELING OF ACTIVE METAL IONS THROUGH THIN ALUMINUM FILMS - Yorkulov Ruslan (American Journals, 2024)
Spatial distributions of ions (K+, Na+) passed through thin single-crystal Al films with thicknesses from 180 to 600 Å and critical channeling angles were studied. Ion energy varied within E0 = 10−30 keV. It was shown that increasing the primary ion beam energy leads to a decrease in the width of the angular distribution maxima, which is associated with a decrease in the critical channeling angle ψcr. It was found that ψcr for axial channeling does not exceed 4−5◦, and for planar channeling — 9−10◦.
Keywords: Critical angle, ion passage, angular distribution, channeling, spatial distribution.